2020
DOI: 10.1029/2020ef001607
|View full text |Cite
|
Sign up to set email alerts
|

Sea Level Rise Driving Increasingly Predictable Coastal Inundation in Sydney, Australia

Abstract: As global mean sea level continues to rise, thresholds corresponding to coastal inundation impacts are exceeded more frequently. This paper aims to relate sea level rise (SLR) observations and projections to their physical on-the-ground impacts. Using a large coastal city as an example, we show that in Sydney, Australia, frequencies of minor coastal inundation have increased from 1.6 to 7.8 days per year between 1914 and present day. We attribute over 80% of the observed coastal inundation events between 1970 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…Australia's coast is also particularly vulnerable to the effects of climate change with increases in sea level, changes in wave climate and storminess, and ocean warming all expected to have significant and, in some areas, above global average impacts in Australia (Department of Climate Change, 2009;Gurran et al, 2011;Ranasinghe, 2016;IPCC, 2019). Indeed, these impacts are beginning to emerge (e.g., Harley et al, 2017;Hanslow et al, 2019;Hague et al, 2020) and are forecast to escalate in coming decades (e.g., Kinsela et al, 2017;Hanslow et al, 2018;Holper et al, 2018;Seashore Engineering, 2019;Ware et al, 2020). Consequently, it is essential to identify the key research priorities that will allow societies to address these major global challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Australia's coast is also particularly vulnerable to the effects of climate change with increases in sea level, changes in wave climate and storminess, and ocean warming all expected to have significant and, in some areas, above global average impacts in Australia (Department of Climate Change, 2009;Gurran et al, 2011;Ranasinghe, 2016;IPCC, 2019). Indeed, these impacts are beginning to emerge (e.g., Harley et al, 2017;Hanslow et al, 2019;Hague et al, 2020) and are forecast to escalate in coming decades (e.g., Kinsela et al, 2017;Hanslow et al, 2018;Holper et al, 2018;Seashore Engineering, 2019;Ware et al, 2020). Consequently, it is essential to identify the key research priorities that will allow societies to address these major global challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have further shown that the height of ESLs could increase further than that which will occur due to global mean sea level (GMSL) rise in some locations (Pickering et al 2017;Devlin et al 2017;Harker et al 2019;Muis et al 2020;Meucci et al 2020). For example, research has noted the importance of understanding the contribution of storms (Stephens et al 2020), astronomical tides (Hague et al 2020) and wave climate conditions (O'Grady et al 2019a) to the total water level and resulting coastal impacts (Church et al 2006;Ranasinghe 2016;Hague et al 2020). Individually, each factor may not be considered extreme but can compound to an ESL event which causes greater impact to the coast (Church et al 2006;Hague et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…McInnes et al 2016;O'Grady et al 2019a;Meucci et al 2020;Kirezci et al 2020) or their impact (e.g. Hague et al 2019Hague et al , 2020, with both approaches giving unique insights into the spatial and temporal scales of events. Climate change is likely to change ESL drivers, which, particularly in concurrence with rising mean sea level, will result in an increase in adverse/damaging coastal impacts (Church et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations